Zooplankton composition, abundance and diversity in different biotopes associated with Arowana aquaculture - Md. Lajis, Nurulhuda (2013)
This study is an effort to determine composition, abundance and diversity of zooplankton in three different biota (lake, canal and Arowana aquaculture pond) for 6 months period from March 2013 until August 2013. This study was conducted at Bukit Merah Lake, Perak (longitude of 5°2’00’’ and latitude 100°40’00’’). Physical-chemical parameters were recorded in situ using YSI multiparameter probe (Model 57). Water samples for nutrient analysis (NO3-N, NO2-N and PO4-P) were collected using Van Dorn horizontal water sampler. Zooplankton samples were collected using standard zooplankton plankton net (35μm mesh size). Physical-chemical parameter and nutrient data were analyzed using SURFER 10 Golden Software. Zooplankton diversity index and species evenness were analyzed using PRIMER software package (version 6.1.9, PRIMER-E Ltd.) and SPSS (Statistical Package for the Social Sciences. Version 16) was used to determine significant difference and correlation between each of these factors. Zooplankton group consists of Rotifera (9 families), Copepoda (Cyclopoid and Calanoid) and Cladocera (2 families) were found in the study area. The zooplankton community was dominated by Rotifera that was smaller size compared to Copepoda and Cladocera. This could be due to the predation by fish that prefer larger size of zooplankton. Rotifera was significantly correlated with water temperature (p<0.01) and some indicator species (Branchionus spp., Keratella spp. and Trichocerca spp.) were present in low density. The diversity index and species evenness was highest in the canal. In conclusion, density of zooplankton was higher at lake and pond compared to the canal.